Alphabet Books: Relations Between Aspects of Parent-Child Shared Reading, Children's Motivation, and Early Literacy Skills. Issue 4 (19th May 2021) - Bergman Deitcher, Deborah; Aram, Dorit; Itzkovich, Inbar
Abstract: The study examined aspects of parent-child shared reading interactions of two Hebrew alphabet books, children's motivation to engage in early literacy activities, and how these variables relate to children's early literacy skills. Participants were 44 children (32 girls, 12 boys) aged 4.6 to 6.6 years ( M  = 5.6, SD  = 0.54) and one parent (42 mothers, 2 fathers). Results revealed that parents made more references to the writing system than to the content or illustrations in the books, which was positively related to children's early literacy skills. Children were highly motivated to engage in literacy activities, which were related to their skills. Yet shared reading contributed to children's early literacy skills, beyond motivation. Across various languages, including alphabet books in shared reading interactions may help support children's early literacy development.